Right Ventricular Infarction Secondary to Extensive Bilateral Pulmonary Emboli in the Setting of Negative D-dimer: A Case Report and Mini-Review - Yazdanpanah, Fariba; Zaim, Bulent; Hunter, Charles; Anderson, Robyn; Bahl, Vivek (Cardiology and Cardiovascular Medicine, 2022)
Introduction: Acute pulmonary embolism (PE) is one of the presentations of venous thromboembolism (VTE) which can be potentially life-threatening by causing cardiovascular collapse. Commonly, a negative D-dimer assay is accepted for ruling out PE; however, there have been cases such as this case that challenge current practice. Case presentation: This case report presents an 83-year-old female with sudden onset shortness of breath associated with low oxygen saturation on the physical exam. Initial workup revealed elevated levels of troponin-T and pro-B-type natriuretic peptide with preliminary normal D-dimer assay. At the start, the patient managed as Right Ventricular (RV) infarction with remarkable findings of RV dysfunction and pressure overload in transthoracic echocardiogram. Eventually chest CT angiogram documented extensive bilateral pulmonary emboli (PE), and interestingly, D-dimer became positive 5 days after the diagnosis of PE. Conclusions: This case report is a rare case of initial negative D-dimer in the setting of extensive bilateral PE which caused right ventricular infarction. The literature review demonstrated only a few cases of PE in the setting of negative D-dimer. This unusual clinical scenario presents a diagnostic challenge in patients with low or moderate clinical probability for PE; even some current practices indicate stopping further diagnostic work-up if the D-dimer is negative in these groups. To mitigate negative outcomes in patients with low or moderate clinical probability, other strategies have been proposed to make an early diagnosis of PE such as triple combination modalities; however, they require additional analysis and consideration before they can be routinely recommended.